2016
DOI: 10.1002/polb.24096
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of small molecules in zwitterionic polymers

Abstract: Despite great interests in using zwitterionic polymers for membrane surface modification to enhance antifouling properties, there lacks fundamental understanding of the relationship between polymer structure and water/salt separation properties. In this study, two series of zwitterionic polymers were prepared from sulfobetaine methacrylate and 2‐methacryloyloxyethyl phosphorylcholine. Both are crosslinked by poly(ethylene glycol) diacrylate (PEGDA). These copolymers were thoroughly characterized in terms of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…Zwitterionic materials contain both positively- and negatively-charged groups and have neutral charge [58,59,60,61]. Figure 9 shows typical zwitterionic polymers containing betaine groups, which have been widely investigated as antifouling materials to decrease protein adhesion.…”
Section: Membrane Surface Modification Using Hydrophilic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zwitterionic materials contain both positively- and negatively-charged groups and have neutral charge [58,59,60,61]. Figure 9 shows typical zwitterionic polymers containing betaine groups, which have been widely investigated as antifouling materials to decrease protein adhesion.…”
Section: Membrane Surface Modification Using Hydrophilic Materialsmentioning
confidence: 99%
“…Therefore, zwitterions can be more hydrophilic than PEG [58,62]. A study of copolymer hydrogels prepared from PEGDA and zwitterionic monomer, such as sulfobetaine methacrylate (SBMA), exhibit greater hydrophilicity than those from PEGDA [61,63,64]. Similar to PEG, zwitterionic chains have elastic forces against foulants when they compress the chains, which also contributes to antifouling properties [65].…”
Section: Membrane Surface Modification Using Hydrophilic Materialsmentioning
confidence: 99%
“…[ 28 ] Studies have reported that copolymer hydrogels prepared by poly(ethylene glycol)diacrylate (PEGDA) and zwitterionic monomer, such as carboxybetaine methacrylate and sulfobetaine methacrylate (SBMA), demonstrate better hydrophilicity than those of PEGDA. [ 29,30 ] Most of the zwitterionic materials are coated onto the surface of various substrates to enhance the hydrophilicity. [ 31–33 ] It is reported that coatings by the simultaneous deposition of PDA with PMPC can enhance the biocompatibility, hydrophilicity, and fouling resistance of the silicon wafers.…”
Section: Figurementioning
confidence: 99%
“…Betaine-based zwitterionic materials have emerged as a new platform with superior antifouling properties against proteins, such as phosphobetaine (with PO 4 – ), carboxybetaine (with COO – ), and sulfobetaine (with SO 3 – ). , Despite neutral charges, the zwitterions generate a strong hydration layer on the surface through electrostatic force and hydrogen bonding, yielding superior antifouling properties. In particular, poly­(methacryloyloxyethyl phosphorylcholine) (pMPC) has a structure similar to phospholipid cell membranes, and it has been widely studied. , The low fouling nature of the zwitterionic surface has been adopted to develop antifouling membranes with stable permeance using a variety of techniques. , For example, copolymers containing zwitterionic components can be used to prepare membranes with the zwitterionic surface; ,, zwitterionic materials can also be grafted or coated on the membrane surface. ,, …”
Section: Introductionmentioning
confidence: 99%